SIMULTANEOUS DETERMINATION OF IRON(II) AND IRON(III) BY DERIVATIVE SPECTROPHOTOMETRIC METHOD - Zulfiani, Puji
Derivative spectrophotometric method based on zero-crossing technique in simultaneous determination of iron(II) and iron(III) has been proposed. 1,10-phenantroline and sodium thiocyanate as a chromogenic reagent were used, and measurements were carried out at pH 1. Both complexes were formed immediately and were stable for at least 1 hour. The normal, first-, second-, and third- derivative spectra were recorded for these ion either alone or in binary mixtures. A first derivative spectrum was selected for evaluation because working wavelenght determination was more precise. The amplitude of derivative spectra was measured at wavelengths of 454 nm for determination of iron(II) and 510 nm for iron(III). Analytical performance of this developed method showed a good precision (%CV= 3,16 % for iron(II) and 2,05% for iron(III)) with limits of detection = 0,25 ?g mL-1 for iron(II) and 2,68 ?g mL-1 for iron(III). Linearity was obtained in the range 0,4 - 2,4 ?g mL-1 for iron(II) and 2 - 12 ?g mL- for iron(III). The average percentage recoveries are 97,50% and 103,17% for iron(II) and iron(III), respectively.